Facing Some Environmental Aspects Of Coal Mining - Induced Ground Subsidence: Optimum Planning Of Highways And Coal Exploitation In Poland - V. Kontogianni (Society for Mining, Metallurgy & Exploration, 2006)
The underground extraction of coal is associated with ground movements extending from the mining area to the ground surface, which result in bowls of ground subsidence, with amplitude exceeding the amount of several meters and occasionally with important tilt and curvature of ground surface. Such changes at both the underground environment and surface topography lead to destruction of buildings, failure of utilities and transportation networks, and occasionally formation of areas vulnerable to flooding, or even small pools. Based on geodetic surface measurements of ground elevation changes, various theories and empirical models relating surface subsidence with the geometry of underground voids formed have been proposed, and predictions of expected subsidence in the form of contours have been estimated. In this study a case study of planning of a new highway network through areas in which coal extraction was also planned is discussed. This work is partly funded by EU. The optimum solution selected was a modification of the initial highway planning, so that the road is increased in length and by-passes the richest coal-field, where maximum post-exploitation subsidence was predicted, and only crosses either minor coalfields, which are not to be exploited, or even margins of main coalfields, in which minor post-exploitation subsidence is expected.